Transcriptional coregulator SNW/SKIP: the concealed tie of dissimilar pathways - Folk, P; Půta, F; Skruzný, M (Cellular and molecular life sciences, 2004)
Eukaryotic gene expression requires that all the steps of messenger RNA production are regulated in concert to integrate the diverse inputs cells receive. We discuss the functioning of SNW/SKIP, an essential spliceosomal component and transcriptional coregulator, which may provide regulatory coupling of transcription initiation and splicing. SNW/SKIP potentiates the activity of important transcription factors, such as vitamin D receptor, CBF1 (RBP-Jkappa), Smad2/3, and MyoD. It synergizes with Ski in overcoming pRb-mediated cell cycle arrest, and it is targeted by the viral transactivators EBNA2 and E7. SNW/SKIP may aid in conformational transition of the gene expression machine through its avidity to nuclear matrix fractions or by recruiting foldases such as the prolyl isomerase PPIL1. The extensive list of SNW/SKIP partners, its unique primary structure, conserved from yeast to humans, and its essential character suggest a distinct function of general importance.
Keywords: genetická transkripce; signální transdukce; Signal Transduction; sestřih RNA; DNA-Binding Proteins; Humans; DNA vazebné proteiny; regulace genové exprese; Transcription Factors; Transcription, Genetic; Nuclear Receptor Coactivators; jaderné proteiny; lidé; zvířata; Transcriptional Activation; Trans-Activators; aktivace transkripce; Gene Expression Regulation; trans-aktivátory; Nuclear Proteins; RNA Splicing; koaktivátory jaderných receptorů; transkripční faktory; Animals; terciární struktura proteinů; Protein Structure, Tertiary